264 Stress fractures during top-level international athletics championships. (3rd March 2020) - Edouard, Pascal; Vinther, Anders
Abstract : Background: Stress fracture is a frequent injury among athletics athletes. During international Athletics championships, although stress fractures represented a small percentage of all injuries (2.9% of all injuries and 4.9% of in-competition time-loss injuries for female athletes), it exists and should not be neglected, because it could be one symptom of Relative Energy Deficiency in Sport. Objective: To specifically analyse stress fractures during top-level international Athletics championships from 2007 to 2019. Design: Prospective study. Setting: 21 international championships from 2007 to 2019. Participants: 26281 (14130 male and 12151 female) international-level registered athletes. Main outcome measurements: The national medical team and the local organizing committee physicians reported all injuries daily on a standardised injury report form during 21 international championships. Only stress fractures were included in the descriptive analysis. Results: During the 21 international athletics championships, a total of 36 stress fractures were reported, representing 1.6% of all reported injuries. 14 were in male and 22 in female athletes, and 54% in endurance and 46% in explosive disciplines. The overall stress fracture incidence was 1.4 per 1000 registered athletes (95%CI=1.0–1.8). The relative risk was almost doubled in female compared to male athletes although this was not statistically significant (relative risk (RR)=1.83, 95%CI=0.94–3.57). Most of stress fractures involved the lower extremity (92%). In female athletes, 46% were located at the lower leg and 41% at the foot, compared to 14% and 64%, respectively for male athletes. More than half of the stress fractures were classified as severe injuries (i.e. estimated number of days of absence >28 days). Conclusions: Stress fractures also occurred during major international athletics championships, representing a severe injury, with sex differences in location and most likely also in overall risk.